Free electron lasers 2002 : proceedings of the 24th International Free Electron Laser Conference and the 9th FEL Users Workshop, Argonne, Illinois, U.S.A., September 9-13, 2002 /: proceedings of the 24th International Free Electron Laser Conference and the 9th FEL Users Workshop, Argonne, Illinois, U.S.A., September 9-13, 2002. (2003) - Unknown
No abstract available